1998
DOI: 10.1159/000007531
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hepatocellular Carcinoma

Abstract: Treatment of hepatocellular carcinoma (HCC) remains a critical issue particularly in the endemic areas. This paper summarizes the literature in the recent 4 years and the author’s data. Substantial progress has been found in the treatment of HCC during the recent decades, which was mainly a result of advances in medical imaging, aggressive surgical approach, regional cancer therapies and multidisciplinary approach. Surgical approaches that resulted in significant prolonged survival included: resection (particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The mean tumor volume before (V1) and after (V2) treatment was 0.0355 cm 3 and 0.2248 cm 3 in group A, 0.0374 cm 3 and 0.0573 cm 3 in group B, 0.0380 cm 3 and 0.3674 cm 3 in group C, respectively. The mean ratio (V2/V1) was 6.2791 in group A, 1.5324 in group B and 9.1382 in group C. Compared with the control group (group C), group B showed significant inhibition of tumor growth (P<0.01), while group A did not (P>0.05).…”
Section: Resultsmentioning
confidence: 96%
“…The mean tumor volume before (V1) and after (V2) treatment was 0.0355 cm 3 and 0.2248 cm 3 in group A, 0.0374 cm 3 and 0.0573 cm 3 in group B, 0.0380 cm 3 and 0.3674 cm 3 in group C, respectively. The mean ratio (V2/V1) was 6.2791 in group A, 1.5324 in group B and 9.1382 in group C. Compared with the control group (group C), group B showed significant inhibition of tumor growth (P<0.01), while group A did not (P>0.05).…”
Section: Resultsmentioning
confidence: 96%
“…The mean greatest transverse tumor diameter measured by CT or MRI was 7.2, 8.3, and 7.9 cm for each group, respectively. Fourteen patients presented with portal vein thrombosis (3,8, and 3 in groups 1-3, respectively). All three groups had comparable proportions of hypervascular tumors (89%, 93%, 94% for each group, respectively).…”
Section: Study Groupsmentioning
confidence: 99%
“…Despite the development of new treatment modalities, clinical outcomes are typically poor. Few therapeutic options are effective, especially since neither conventional systemic chemotherapy nor radiation therapy can halt the progression of disease [1][2][3]. Transcatheter arterial chemoembolization (TACE), which consists of delivering a mixture of ethiodized oil, chemotherapeutic agents and embolic particles directly to the tumor, is commonly performed to treat these types of liver cancer.…”
mentioning
confidence: 99%
“…1,2 Epidemiological studies in high-risk populations have identified chronic hepatitis B or C virus infections as well as dietary exposure to aflatoxin B1 as major factors in the etiology of this disease. 3 The genesis of human cancers is a multistep process reflecting cumulative genetic alterations that include activation of oncogenes or inactivation of tumor suppressor genes.…”
mentioning
confidence: 99%